Fatigue reliability evaluation of aging prestressed concrete bridge accounting for stochastic traffic loading and resistance degradation - Luo, Yuan; Zheng, Hui; Zhang, Haiping; Liu, Yang (Advances in structural engineering, 2021)
Fatigue damage accumulation is a critical factor resulting in the failure of prestressed concrete (PC) bridges. The fatigue damage is usually caused by the coupled effect of cyclic vehicle loading and environmental corrosion. This study investigated probabilistic fatigue damage on aging PC bridges considering both stochastic traffic loading and corrosion. A stochastic traffic model was derived based on long-term monitoring data aiming to simulate fatigue stress spectra of critical rebar. The effect of cracks on the fatigue stress spectra was investigated in order to model the fatigue stress state more realistically. A three-stage traffic growth model was established based on traffic volume histories of three highways in China. A fatigue limit state function considering traffic growth and corrosion effect was deduced for fatigue reliability assessment of PC bridges. Numerical results show that the stress amplitude of rebar considering cracks is 1.53 times greater than the rebar with no-cracks, resulting in a decrease of fatigue life by 68 years. In addition, the three-stage traffic growth models lead to 25 years shorter fatigue life than the one considering a linear traffic growth model. Finally, the corrosion effect results in a fatigue life of 44 years. The numerical results provide a theoretical basis for fatigue life estimation and maintenance of aging PC bridges.